The Natural History of pT1 Colorectal Cancer - Risio, Mauro (Frontiers in Oncology, 2012)
Colorectal carcinoma invading the submucosa but not the muscular layer (pT1, early invasive cancer) represents the earliest form of clinically relevant colorectal cancer in most patients. Neoplastic invasion of the submucosa, in fact, opens the way to metastasis via the lymphatic and blood vessels, and the choice between surveillance and major surgery will turn on its metastatic potential. The following histological features predict the risk of metastasis and the different clinical outcomes: grade of differentiation of carcinoma, lymphovascular invasion, state of the resection margin. Microstaging of invasive cancer, namely the width and the depth of submucosal invasion, together with tumor budding at the advancing edge allow the metastatic risk to be further stratified in minimal, low, and high. Different, although morphologically undistinguishable, tumorigenic pathways are supposed to lead to the malignant transformation of colonic mucosa and subsequently drive the progression from early to advanced cancer: new biomarkers are needed to identify progressive and non-progressive pT1 neoplasia.